Outcomes of proximal fibular osteotomy in osteoarthritis knee - Tejura, Mihir A.; Sonawane, Darshankumar N. (International Journal of Research in Orthopaedics, 2024)
The need for management of mild to moderate osteoarthritis (OA) knee surgically with a new method that is relatively simple, less invasive, less expensive and suitable for Indian setting postulated to offer short to medium term relief and defers the need for a major surgery like total knee replacement was served by a novel surgical technique of proximal fibular osteotomy (PFO). The aim of this study is to evaluate the efficacy, functional outcomes and complications of PFO in OA of knee joint. Total 20 patients (33 knees) with OA knee operated by PFO were included in the study and were followed up at 1 month, 3 months and 6 months postoperatively. The outcomes of PFO were evaluated using VAS score, functional american knee society score and Kellgren Lawrence (KL) scale and the patients were evaluated post-operatively for development of any complication and it’s improvement at each follow up. The results showed significant improvement in efficacy and functional outcomes with respect to VAS score and functional American knee society score however there was no significant change in KL scale grading postoperative. Few patients developed EHL weakness and hypoaesthesia post-operatively which gradually improved at further follow ups. This study concludes that PFO is a safe and efficacious method of management of OA knee showing significant pain relief and improving functional outcomes of patient significantly.